GLOBAL SATELLITE MONITORING USING METHOD OF SPATIAL INTERPOLATION OF KOLMOGOROV FOR STUDY OF ASSESSMENT OF ATMOSPHERIC CONCENTRATION OF CO2 - Даргейко, Л. Ф.; Лялько, В. И.; Федоровский, А. Д.; Костюченко, Ю. В.; Артеменко, И. Г. (Scientific Centre for Aerospace Research of the Earth Institute of Geological Science National Academy of Sciences of Ukraine, Kyiv, Ukraine, 2014)
For optimization of data for global satellite environmental and climate monitoring the method of spatial interpolation of Kolmogorov is validated in this paper. As the source data the global map of carbon dioxide atmospheric concentration obtained from SCIAMACHY sensor of Envisat71 satellite has been utilized.